MIDDLE MIOCENE OSTRACODS FROM THE SALENTINE PENINSULA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The ostracod faunas of the S. Caterina and S. Maria al Bagno sections (Salentine Peninsula, Apulia) were studied. These sections comprise the lower and middle levels of the Pietra Leccese formationand range collectively from the uppermost Burdigalian or the lower Langhian to the middle Serravallian. Forty-one species, belonging to twenty-seven genera were identified. Nineteen species known previously are illustrated and discussed; six (Carinocythereis messapica n. sp., Celtia multicostata n. sp., Cytherella obesa n. sp., Cytherella polygonalis n. sp., Cytherella salentinensis n. sp. and Cytherelloidea ? rectangularisn. sp.) are described as new, and two are left in open nomenclature. The stratigraphic distribution of a remarkable number ofshelf ostracod species,known previously from the Upper Miocene upwards, includes also part of the Middle Miocene.